2011
DOI: 10.1016/j.jneumeth.2011.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescent cells in rat brain can be convincing impostors in green fluorescent reporter studies

Abstract: Cell transplant and gene therapies are promising approaches to many disorders of the nervous system. In studies involving cell transplants to the brain or nervous system, expression of green fluorescent protein (GFP) is commonly used to label cells, allowing their identification and histological assessment even after long post-operative survival times. Techniques employing viral tracing or reporter genes also commonly use GFP to label cells. Here, we document the presence of a subpopulation of green autofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…After deparaffinization, antigen retrieval, sodium borohydride treatment, CuSO 4 treatment, and blocking, the slides were treated with primary antibodies for 16 hr, then with secondary fluorescent antibodies for 1 hr, followed by brief DAPI staining and sealing with antifade. Sodium borohydride and CuSO 4 were used to minimize autofluorescence by Shiff‐base and by Lipofuscin, respectively (Schnell, Staines, & Wessendorf, 1999; Spitzer, Sammons, & Price, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…After deparaffinization, antigen retrieval, sodium borohydride treatment, CuSO 4 treatment, and blocking, the slides were treated with primary antibodies for 16 hr, then with secondary fluorescent antibodies for 1 hr, followed by brief DAPI staining and sealing with antifade. Sodium borohydride and CuSO 4 were used to minimize autofluorescence by Shiff‐base and by Lipofuscin, respectively (Schnell, Staines, & Wessendorf, 1999; Spitzer, Sammons, & Price, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Unspecific cellular/tissue autofluorescence with broad excitation/emission may arise from lipofuscin accumulation with aging, typically causing a speckled cytosolic staining (41,49,50). Other potential sources of autofluorescence, which even persist tissue fixation, are NADH and serotonin (50).…”
Section: Interference Of Cellular and Tissue Autofluorescencementioning
confidence: 99%
“…Other potential sources of autofluorescence, which even persist tissue fixation, are NADH and serotonin (50). As such background fluorescence may interfere with roGFP1 imaging, we compared nontransgenic wild-type CCD, chargecoupled device; CTX, cortex; DG, dentate gyrus; HP, hippocampus; IC, inferior colliculus; roGFPc, cytosolically expressed roGFP; STR, striatum; S1, primary somatosensory cortex; TH, thalamus; VIS, visual cortex; Str.…”
Section: Interference Of Cellular and Tissue Autofluorescencementioning
confidence: 99%
“…Autofluorescence, either intrinsic or induced by fixation reagents and tissue processing, may mask specific fluorescent signals or be mistaken for fluorescent labels [16,17]. Autofluorescence of neural tissue often complicates the use of the green fluorescent protein (GFP) [18]. More importantly for our research, animals with spinal cord transection showed significant autofluorescence of cortical, brainstem, and spinal cord neurons, which interferes with identification of labeling [19,20].…”
Section: Introductionmentioning
confidence: 92%